Square-Root Dierential Equations for Dark Matter Particles - Kh, Namsrai; B, Munkhzaya (Scientific transaction of the National University of Mongolia. Physics, 2022)
We propose the square root operator formalism for description of motion for a dark particle candidate. It turns out that such type particle moves randomly and lls in whole space. It seems that such particles do not create material structure of universe, like atoms, molecules, stars, planets and etc. due to their stochastic motion.